Possessed : hypnotic crimes, corporate fiction, and the invention of cinema - Andriopoulos, Stefan (Cinema and modernity., 2008)
Silent cinema explored themes of mesmerism, possession and corporate bodies that subsumed individual identities. At the same time, critics were accusing film itself of exerting a hypnotic influence over its audience. This book shows that this anxiety over being governed by an outside force was a pervasive concern of the period.